Potency of marbofloxacin for pig pneumonia pathogens Actinobacillus pleuropneumoniae and Pasteurella multocida: Comparison of growth media. (April 2017) - Dorey, L.; Hobson, S.; Lees, P.
Abstract: Pharmacodynamic properties of marbofloxacin were established for six isolates each of the pig respiratory tract pathogens, Actinobacillus pleuropneumoniae and Pasteurella multocida . Three in vitro indices of potency were determined; Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and Mutant Prevention Concentration (MPC). For MIC determination Clinical Laboratory Standards Institute guidelines were modified in three respects: (1) comparison was made between two growth media, an artificial broth and pig serum; (2) a high inoculum count was used to simulate heavy clinical bacteriological loads; and (3) five overlapping sets of two-fold dilutions were used to improve accuracy of determinations. Similar methods were used for MBC and MPC estimations. MIC and MPC serum:broth ratios for A. pleuropneumoniae were 0.79:1 and 0.99:1, respectively, and corresponding values for P. multocida were 1.12:1 and 1.32:1. Serum protein binding of marbofloxacin was 49%, so that fraction unbound (fu) serum MIC values were significantly lower than those predicted by correction for protein binding; fu serum:broth MIC ratios were 0.40:1 ( A. pleuropneumoniae ) and 0.50:1 ( P. multocida ). For broth, MPC:MIC ratios were 13.7:1 ( A. pleuropneumoniae ) and 14.2:1 ( P. multocida ). Corresponding ratios for serum were similar, 17.2:1 and 18.8:1, respectively. It is suggested that, for dose prediction purposes, serum data might be preferable to potency indices measured in broths. Highlights: Pharmacodynamic indices of potency of marbofloxacin (MIC, MBC, MPC) were bacterial species dependent. Pharmacodynamic indices of potency of marbofloxacin (MIC, MBC, MPC) were growth matrix dependent. Serum/broth differences in potency may influence PK/PD approaches to dose determination in future studies.